Procedural pain in neonatal units in Kenya. Issue 6 (4th July 2014) - Kyololo, O'Brien Munyao; Stevens, Bonnie; Gastaldo, Denise; Gisore, Peter
Abstract : Objectives: To determine the nature and frequency of painful procedures and procedural pain management practices in neonatal units in Kenya. Design: Cross-sectional survey. Setting: Level I and level II neonatal units in Kenya. Patients: Ninety-five term and preterm neonates from seven neonatal units. Methods: Medical records of neonates admitted for at least 24 h were reviewed to determine the nature and frequency of painful procedures performed in the 24 h period preceding data collection (6:00 to 6:00) as well as the pain management interventions (eg, morphine, breastfeeding, skin-to-skin contact, containment, non-nutritive sucking) that accompanied each procedure. Results: Neonates experienced a total of 404 painful procedures over a 24 h period (mean=4.3, SD 2.0; range 1–12); 270 tissue-damaging (mean=2.85, SD 1.1; range 1–6) and 134 non-tissue-damaging procedures (mean=1.41, SD 1.2; range 0–6). Peripheral cannula insertion (27%) and intramuscular injections (22%) were the most common painful procedures. Ventilated neonates and neonates admitted in level II neonatal units had a higher number of painful procedures than those admitted in level I units (mean 4.76 vs 2.96). Only one procedure had a pain intensity score documented; and none had been performed with any form of analgesia. Conclusions: Neonates in Kenya were exposed to numerous tissue-damaging and non-tissue-damaging procedures without any form of analgesia. Our findings suggest that education is needed on how to assess and manage procedural pain in neonatal units in Kenya.